2009
DOI: 10.1080/07315724.2009.10719792
|View full text |Cite
|
Sign up to set email alerts
|

Can a Dairy-Rich Diet Be Effective in Long-Term Weight Control of Young Children?

Abstract: We suggest that in addition to lifestyle changes, an isocaloric diet rich in dairy products may be a well-accepted regimen and can be a safe and practical strategy for weight control in young, overweight children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(89 citation statements)
references
References 38 publications
3
86
0
Order By: Relevance
“…This study yielded similar results to those of other studies: when diet and PA goals are realistic and attainable, treatment groups experience a decrease in BAZ 12,24 while control groups experience an increase. 25 Similarly, the magnitude of reductions in BAZ were greater in children randomized to higher dairy intakes, 12 however unique to this study was the addition of weight-bearing PA. To our knowledge, this was the first intervention in obese children to include a biochemical analysis of saturated fatty acids to complement dietary intake assessments. 19,26 Although ModTx were guided to increase servings of dairy, C15:0 decreased at six months.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This study yielded similar results to those of other studies: when diet and PA goals are realistic and attainable, treatment groups experience a decrease in BAZ 12,24 while control groups experience an increase. 25 Similarly, the magnitude of reductions in BAZ were greater in children randomized to higher dairy intakes, 12 however unique to this study was the addition of weight-bearing PA. To our knowledge, this was the first intervention in obese children to include a biochemical analysis of saturated fatty acids to complement dietary intake assessments. 19,26 Although ModTx were guided to increase servings of dairy, C15:0 decreased at six months.…”
Section: Discussionsupporting
confidence: 78%
“…Based on previous studies, 12,23 116 overweight or obese children were needed to provide 80% power at a 5% significance CONSORT diagram for the MY LIFE study…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other measures in which convergent validity was assessed included the EES-C 77 and the Toddler Snack Food Feeding Questionnaire (TSFFQ). 82 The EES-C was compared with data from the QEWP (Spitzer 1992 95 ). Authors reported good convergent validity and show that those with loss of control (LOC) (from QEWP) had higher eating in response to anger, anxiety and frustration and higher depressive symptoms than people without LOC [although results based test for difference (analysis of covariance -ANCOVA), p < 0.05].…”
Section: Eating Behaviourmentioning
confidence: 99%
“…A randomized clinical trial designed to investigate the long-term impact of a diet rich in dairy products on generalized and abdominal obesity in 5-6-year-old children was carried out by Kelishadi and colleagues [102]. In addition to participating in educational sessions on healthy lifestyle (control group), children in a second group received an isocaloric dairy-rich diet (>800 mg calcium/day), while a calorie-restricted diet was applied in the third group.…”
Section: Milk and Dairy Productsmentioning
confidence: 99%